“Evaluación de características de solución para tinturado sólido usando colorantes naturales en rosa (rosa sp.) variedad véndela, cantón Latacunga provincia Cotopaxi 2017” - Quinaucho Quinaucho, Edison Cecilio (2017)
In the present investigation with the theme "Evaluation of Characteristics of solution for solid dyeing using natural colorants in Rosa (Rosa sp.) Véndela Variety, Canton Latacunga Cotopaxi Province 2017 ", in the flower shop SANBEL FLOWERS, Aláquez, Cotopaxi, is focused on the demand of innovative products that today presents the national and international market of flowers, for this reason we carried out the present work with the purpose of taking advantage of the new ways of exporting roses changing from the traditional to the innovative as is the process of organic dyeing of flowers fresh Since it is a research project that is based on responding to an edible need and so to make known an organic flower in the whole face in order that the rose be consumed, which will allow to obtain new flowers dyed of natural form, in addition it will allow launch a new option of roses in the national and international market. For this, three types will be chosen of natural dyes which are applied in the variety Véndela, by levels or degrees of temperatures, obtaining the required data to elaborate the graph of the coloration curve of the pink, present within the object of study to subsequently obtain the required results in the draft.